Hyperactivity in children with psychiatric disorders at Dr George Mukhari Hospital child psychiatry unit - Manyage, Tshilidzi Jane. (My University, 2014)
Background Child and adolescence mental health is a huge concern throughout the world, especially in developing countries were children and adolescence form majority of the population. Hyperactivity is one of the most common behavioural problems seen in child and adolescent psychiatric outpatient units. This behavioural problem may be accompanied by an underlying childhood psychiatric disorders. Objectives To determine the number of children with hyperactivity, establish gender differences, as well as profile of psychiatric disorders associated with hyperactivity at Dr George Mukhari Hospital child psychiatry outpatient unit. Method This was a retrospective descriptive study that included children who presented for the first time at Dr George Mukhari outpatient child psychiatry outpatient unit from January 2009 to December 2009. Children of all genders were equally considered and were within the age group of 3 to 14 years. Data of all children included was collected from the children’s records. All the records of children with hyperactivity were separated from those without this behavioural problem. Gender differences as well as underlying psychiatric disorders were determined. Diagnoses made during the first assessment were based on Diagnostic and Statistical Manual of Mental Disorders, 4th edition text revision (DSM IV TR). Results A total of 49 new children who were assessed during the study period were included. Males were over-represented than females, and accounted to 79.49% and 20.4% respectively. Almost half of the children presented with hyperactivity (48.98%). Most of the children with hyperactivity were less 2 than 6 years (50%), followed by school aged group (41.67%) and then adolescents (8.33%). Majority of children with hyperactivity were males (83.33%) than females (16.67%). The most common disorder associated with hyperactivity was mental retardation (62.50%), followed by attention deficit hyperactivity disorder (29.17%); and then mania due to HIV (4.17%) and sensorineural hearing deficit with hyperactivity (4.17%). Conclusion Hyperactivity is a common behavioural problem or complaint at Dr George Mukhari child psychiatry outpatient unit. It is common in males than females, and is associated with underlying childhood psychiatric disorders. Therefore, health professionals should be trained to identify behavioural problems, and community awareness considered since hyperactivity is associated with childhood psychiatric disorders. This is important because early identification and intervention will subsequently yield a good outcome.
Thesis ( M Med ( Psychiatric ) ) -- University of Limpopo (Medunsa Campus), 2012.
Keywords: Adolescent behavior.; Behaviorism.; WS 462 MAN 2012; Adolescent behavior.; Behaviorism.